2019
DOI: 10.3390/ani9080562
|View full text |Cite
|
Sign up to set email alerts
|

Eye Blink Rates and Eyelid Twitches as a Non-Invasive Measure of Stress in the Domestic Horse

Abstract: Physiological changes provide indices of stress responses, however, behavioural measures may be easier to determine. Spontaneous eye blink rate has potential as a non-invasive indicator of stress. Eyelid movements, along with heart rate (HR) and behaviour, from 33 horses were evaluated over four treatments: 1) control—horse in its normal paddock environment; 2) feed restriction—feed was withheld at regular feeding time; 3) separation—horse was removed from visual contact with their paddock mates; and 4) startl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 39 publications
(47 reference statements)
3
54
2
1
Order By: Relevance
“…A hierarchy of behavioural indicators with increasing stress was found in stabled horses [9], which coupled observable behaviours with physiological measures. Indicators might be subtle, for example eye "wrinkling", eyelid "twitches" and blink rate [10,11], or more overt such as bucking, head-tossing or rearing for example [12]. Reference [12], a detailed review of studies of behaviours of ridden horses, also concluded that individual differences between horses and inconsistencies amongst researchers (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A hierarchy of behavioural indicators with increasing stress was found in stabled horses [9], which coupled observable behaviours with physiological measures. Indicators might be subtle, for example eye "wrinkling", eyelid "twitches" and blink rate [10,11], or more overt such as bucking, head-tossing or rearing for example [12]. Reference [12], a detailed review of studies of behaviours of ridden horses, also concluded that individual differences between horses and inconsistencies amongst researchers (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…An earlier study also reported an increase in blinks during stressful situations [16]. However, Merkies et al [17] found instead that full blink diminished during stress. In this study, the increase was only statistically significant for the Co-occurrence method during transportation stress.…”
Section: Discussionmentioning
confidence: 99%
“…Stress induces typical facial expressions in humans [14], but only a few studies of facial expressions during stress have been performed in horses, most focusing on features around the eye [15] or blinking frequency to determine stress. However, there is some controversy on whether the frequency of blinks increases [16] or diminishes [17] during stress. Pain is an internal stressor and the experience of pain may therefore elicit a stress response.…”
Section: Introductionmentioning
confidence: 99%
“…The action takes place in less than half a second [14]. Decreased eye blink rates has recently been associated to occurrence of stress or pain [22]. The Horse Grimace Scale [10] describes "Orbital Tightening: The eyelid is partially or completely closed".…”
Section: Discussionmentioning
confidence: 99%
“…The inner brow raiser (AU101) is also associated to characteristic changes in the eye region. The inner brow raiser is said to create a "triangular eye" or "worry wrinkles" [22,23], an appearance traditionally related to both stress and pain by horse care providers and veterinarians. Per definition, this muscle contraction increases the perceived size of the eye region, but not the aperture of the eye [14].…”
Section: Discussionmentioning
confidence: 99%